Kinematic and Dynamic Analysis of an Eight-bar Mechanism in Carton Forming - Wan Xia; Yuanchao Deng; Junwei Xin (Jixie chuandong)
In the inner box forming station of the high-end carton， an eight-bar mechanism for bending rectangular cardboard strips is designed， and a theoretical analysis and a simulation are carried out to verify whether it can achieve double-sided bending during the carton forming process. Based on the kinematic and dynamic principles of the plane linkage mechanism， the mechanism is analyzed， and the kinematic model and dynamic model in the mechanism are obtained； combined with the actual working conditions， the mechanism is simulated by Adams software. The displacement， velocity and acceleration equations of the key components and the dynamic statics equations of the components， as well as the displacement， velocity， acceleration and the force curves of the key components in the ideal state and under the condition of a rotation pair with clearance are obtained. The curve analysis conclusions obtained by the simulation meet the design requirements and provide a certain reference， thus verifying the certainty of the eight-bar bending mechanism.